1998
DOI: 10.1128/iai.66.6.2660-2665.1998
|View full text |Cite|
|
Sign up to set email alerts
|

Clostridium difficileToxin B Induces Apoptosis in Intestinal Cultured Cells

Abstract: Toxigenic strains of the anaerobic bacterium Clostridium difficile produce at least two large, single-chain protein exotoxins involved in the pathogenesis of antibiotic-associated diarrhea and colitis. Toxin A (CdA) is a cytotoxic enterotoxin, while toxin B (CdB) is a more potent cytotoxin lacking enterotoxic activity. This study dealt with CdB, providing the first evidence that intestinal cells exposed to this toxin exhibit typical features of apoptosis in that a significant proportion of the treated cells di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 38 publications
(35 reference statements)
4
30
0
1
Order By: Relevance
“…14 %), and the occurrence of apoptosis was further confirmed by ladders of DNA fragmentation. These results are in agreement with previous observations in breast-cancer cells and intestinal cultured cells [30,32]. However, studies in human endothelial cells have showed that inactivation of Cdc42 and Rac cannot influence apoptosis, but their inhibition reduces the expression of the anti-apoptotic genes Bcl-2 and Mcl-1 and increases the expression of pro-apoptotic Bid [33].…”
Section: Discussionsupporting
confidence: 92%
“…14 %), and the occurrence of apoptosis was further confirmed by ladders of DNA fragmentation. These results are in agreement with previous observations in breast-cancer cells and intestinal cultured cells [30,32]. However, studies in human endothelial cells have showed that inactivation of Cdc42 and Rac cannot influence apoptosis, but their inhibition reduces the expression of the anti-apoptotic genes Bcl-2 and Mcl-1 and increases the expression of pro-apoptotic Bid [33].…”
Section: Discussionsupporting
confidence: 92%
“…PI staining also occurs at early time‐points and suggests some cells from this population could be going through necrotic cell death or late apoptosis. These results may explain earlier conflicting reports regarding cell necrosis vs. apoptosis in TcdB‐intoxicated cells (Warny and Kelly, 1999; Fiorentini et al. , 1998).…”
Section: Discussionmentioning
confidence: 51%
“…, 2000) reported PARP cleavage in cells treated with TcdB, further suggesting caspase activation during TcdB induced apoptosis. Interestingly, Warny and Kelly (1999) reported finding necrotic cell death in TcdB‐treated THP‐1 monocytes, while Fiorentini et al. (1998) reported that TcdB was a potent inducer of apoptosis in IEC‐6 intestinal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus does not require internalization to be toxic as its α‐toxin which induces pore formation is responsible for the bacteria cytotoxicity. Among the bacterial toxins known to inhibit small GTPases, toxins A and B of Clostridium difficile have been shown to induce apoptosis in intestinal cultured cells (Fiorentini et al ., 1998; Brito et al ., 2002) as well as other cell types (Linseman et al ., 2001; Hippenstiel et al ., 2002). The level of apoptotic signalling initiation has not been clearly established in these studies but apoptotic cell death was mostly interpreted as a direct consequence of Rho GTPases modification.…”
Section: Discussionmentioning
confidence: 99%